Descarte de medicamentos no município de São Gabriel- RS - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The drug residues, also called drug residues, become a challenge for public agencies , due to their incorrect disposal . Once their use is essential, its residues are constantly thrown improperly causing various effects to the environment. Even though there is a law of the State of Rio Grande do Sul, which pharmacies must offer to receive the appropriate medication waste due and provide your correct destination collectors, it is not always being met. Another problem arises with drugs that still meet the expiration date and that are discarded can return to the consumption of the population through reverse flows. The objective of this study is to investigate the pharmacies in the municipality of São Gabriel - RS to verify its suitability to current legislation, which they must carry out the collection of expired drugs providing their correct destination, and also used the reverse logistics as an instrument to minimize generation of medical waste. To meet the objective proposed two models of questionnaires were administered, one facing the managers of pharmacies and the other for the population of the city, where there was a disparity of knowledge on the current law between them, and also the lack of choice for correct disposal in the municipality of São Gabriel.
Keywords: Resíduos fármacos; Legislação - resíduos; Logística reversa; Pharmaceutical Waste; Legislation - Waste; Reverse logistic; CNPQ::CIENCIAS SOCIAIS APLICADAS